Selected presentations of lip enlargement: clinical manifestation and differentiation - Błochowiak, Katarzyna J.; Kamiński, Bartłomiej; Witmanowski, Henryk; Sokalski, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Lip enlargement may be an important symptom of either systemic or local diseases. On the basis of selected age-matched clinical cases we present the possible causes of lip swelling. We describe the most representative symptoms and recommend treatment of these pathologies. We differentiate lip swelling in Miescher syndrome, monosymptomatic form of Melkersson-Rosenthal syndrome, lip swelling in erythema multiforme and Stevens-Johnson syndrome and lip hemangioma and mucous extravasation cyst. We compare different causes of lip edema and indicate the most helpful diagnostic and treatment methods.